Huang Di nei jing su wen : nature, knowledge, imagery in an ancient Chinese medical text, with an appendix, the doctrine of the five periods and six qi in the Huang Di nei jing su wen - Unschuld, Paul U. (Paul Ulrich), 1943- (University of California Press, 2003)
A foundation of Chinese life sciences and medicine, the 'Huang Di Nei Jing Su Wen' is now available in a complete, fully annotated English translation. Also known as 'Su Wen', or 'The Yellow Emperor's Inner Classic', this influential work came into being over a long period reaching from the 2nd century BCE to the 8th century CE.